Ethyl acetate steam detection gas sensor and preparation method thereof

By using porous ZnO nanorod material as a sensitive body and combining with the solution sputtering process to prepare a gas sensor, the problem of difficulty in effectively detecting ethyl acetate in the prior art is solved, and a high selectivity and high sensitivity detection effect is achieved, which is suitable for fruit freshness detection.

CN119619239APending Publication Date: 2025-03-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311183951.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the case where existing metal oxide gas sensors detect mixed gases or interfering gases, it is difficult to effectively identify and detect target components, especially lower ester substances such as ethyl acetate.

Method used

A porous ZnO nanorod material is used as a sensitive body, and a sensitive layer with appropriate film thickness and uniform distribution is prepared through a solution sputtering process to enhance the responsiveness of the material to ethyl acetate gas.

Benefits of technology

It realizes high selectivity and high sensitivity detection of ethyl acetate, can respond effectively at low concentrations (0.1~1ppm), and has the ability to resist other organic vapor interference, and is suitable for detecting fruit freshness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119619239A_ABST
    Figure CN119619239A_ABST
Patent Text Reader

Abstract

The invention discloses an ethyl acetate steam detection gas sensor and a preparation method. The ethyl acetate steam detection gas sensor takes a porous ZnO nanorod material as a sensitive body. And depositing the graphene on the surface of a ceramic tube gold interdigital electrode through a solution sputtering process to prepare the gas sensor for detecting ethyl acetate. The obtained sensor has good response to ethyl acetate steam, and the detectable actual concentration is as low as 1 ppm. In addition, the sensor also has the capability of resisting interference of other organic steam, and has better selective response to ethyl acetate steam. The sensor can be used as a favorable tool for detecting the freshness of fruits such as apples and strawberries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a gas sensor for detecting ethyl acetate vapor and a preparation method thereof, belonging to the technical field of gas sensors. Background Art

[0002] Studies have shown that the quality of many fruits (such as apples, strawberries, etc.) is directly related to the aroma they emit. Therefore, the freshness of these fruits can be fed back by identifying and analyzing the aroma components. These aroma components are mainly low-level esters (mainly ethyl acetate). However, due to the low chemical activity of these low-level esters, it is challenging to detect them with high sensitivity. Gas sensors based on semiconductor metal oxides have been widely used in various fields such as industry, environmental monitoring, and food testing due to their small size, low energy consumption, and good stability. However, due to the limitations of the gas-sensitive mechanism, most metal oxide gas sensors respond to almost a variety of gases. When detecting mixed gases or in the presence of interfering gases, it is difficult to effectively identify and detect the target components. Summary of the invention

[0003] Based on the above problems, the purpose of the present invention is to provide a porous ZnO material as a sensitive body, adopt a solution sputtering process to prepare a sensitive layer with appropriate film thickness and uniform distribution, and thereby prepare a highly selective and highly sensitive ethyl acetate gas sensor.

[0004] In order to make the sensor have unique responsiveness to the target gas, it is necessary to start from the interaction between the material and the gas molecules and study sensitive materials with high selectivity and high sensitivity. Ethyl acetate molecules can undergo specific adsorption and catalytic oxidation reactions on the surface of catalytically active ZnO materials. By creating pores on the ZnO surface, the strength of this interaction can be further enhanced to increase its detection sensitivity.

[0005] According to one aspect of the present application, a gas sensor for detecting ethyl acetate vapor is provided, wherein the gas sensor for detecting ethyl acetate vapor uses a porous ZnO nanorod material as a sensitive body;

[0006] The pore size of the porous ZnO nanorod material is 2 to 50 nm;

[0007] The porous ZnO nanorod material has a length of 2 to 8 μm and a width of 200 to 400 nm.

[0008] Optionally, the operating temperature of the ethyl acetate vapor detection gas sensor is 200-350°C.

[0009] Optionally, the resistance value of the ethyl acetate vapor detection gas sensor is 100 to 2000 KΩ.

[0010] Optionally, the resistance value of the ethyl acetate vapor detection gas sensor is selected from any value of 100KΩ, 200KΩ, 300KΩ, 500KΩ, 1000KΩ, 1500KΩ, 2000KΩ or a range between any two of the above.

[0011] Optionally, the ethyl acetate vapor detection gas sensor can detect an ethyl acetate concentration of 0.1 to 1 ppm.

[0012] According to another aspect of the present application, a method for preparing the above-mentioned ethyl acetate vapor detection gas sensor is provided, the preparation method comprising:

[0013] A solution containing porous ZnO nanorod material is dropped onto the surface of the interdigital electrode, and infrared baking is performed until the solution is completely volatilized to obtain the ethyl acetate vapor detection gas sensor.

[0014] Optionally, the solvent in the solution is selected from at least one of water, ethanol, methanol, acetone, acetonitrile, toluene, ethylene glycol, and n-hexane.

[0015] Optionally, the mass volume ratio of the porous ZnO nanorod material to the solvent is 5-100 mg: 0.5-10 mL.

[0016] Optionally, the number of dripping is 3 to 8 times.

[0017] Optionally, the infrared baking temperature is 50-80°C.

[0018] Optionally, the infrared baking temperature is selected from any value of 50° C., 60° C., 70° C., 80° C., or a range between any two of the above values.

[0019] Optionally, the method for preparing the porous ZnO nanorod material comprises:

[0020] In a sealed container, a mixture containing zinc compounds, urea and a solvent is reacted and annealed to obtain the porous ZnO nanorod material.

[0021] Optionally, the zinc compound is selected from at least one of zinc chloride, zinc nitrate and zinc acetate.

[0022] Optionally, the molar ratio of the zinc compound to urea is 1:0.5-5.

[0023] Optionally, the molar ratio of the zinc compound to urea is selected from any value of 1:0.5, 1:1, 1:1.5, 1:2, 1:4, 1:5 or a range between any two of the above.

[0024] Optionally, the solvent is selected from water and / or ethanol.

[0025] Optionally, the molar volume ratio of the zinc compound to the solvent is 0.06-1.2 mol: 0.5-20 mL.

[0026] Optionally, the reaction temperature is 140-200° C., and the reaction time is 12-20 h.

[0027] Optionally, the annealing temperature is 400-600° C., and the annealing time is 2-4 hours.

[0028] As an implementable technical solution, the technical solution adopted by the present invention is:

[0029] Porous ZnO nanorod materials are synthesized by hydrothermal treatment and annealing of a mixture of zinc compounds, urea and solvent.

[0030] In this application, the preparation method of porous ZnO material, the specific steps are as follows

[0031] 1) The molar ratio of zinc compound to urea is 1:0.5-5;

[0032] 2) Disperse the mixture in 40 mL of deionized water;

[0033] 3) Transfer the entire solution into a 50 mL polytetrafluoroethylene-lined autoclave and keep it at 140-200°C for 12 hours;

[0034] 4) The precipitate was collected by centrifugation and washed with deionized water several times. Finally, it was dried at 60°C overnight and annealed at 400-600°C in air for 2 hours to obtain the product.

[0035] The porous ZnO material is used as the sensitive body, and the thickness of the gas-sensitive film is controlled through a solution sputtering process to optimize the response of the material to ethyl acetate gas.

[0036] The gas sensor is prepared by solution sputtering process. The specific steps are as follows:

[0037] 1) Take a certain mass of porous ZnO material and evenly disperse it in a suitable solvent;

[0038] 2) Take a certain volume of the dispersed porous ZnO material described in step 1) and drop it on the surface of N ceramic tube interdigital electrodes. In order to make the sensitive body evenly deposited on the surface of the interdigital electrodes, it is necessary to place it under an infrared lamp at a certain temperature for baking until the organic solvent is completely volatilized to form a layer of gas sensitive film; by dropping the sensitive body dispersion liquid on different interdigital electrodes for different times and baking temperatures, multiple sensitive films with different thicknesses and film consistency will be obtained;

[0039] 3) The ceramic tube interdigital electrodes described in step 2) are connected to the measuring circuit respectively with two Pt wires, and are connected to the heating circuit with a Ni-Cr alloy wire to provide temperature to the surface of the ceramic tube; the sensor works at 300°C, and the resistance value is 100 to 2000KΩ.

[0040] Optionally, the porous ZnO nanomaterial has a mass of 5 to 100 mg and is dispersed in 0.5 to 10 mL of a solvent by ultrasonic dispersion to form a suspension.

[0041] Optionally, the organic solvent is a mixture of one or more of ultrapure water, ethanol, methanol, acetone, acetonitrile, toluene, ethylene glycol, and n-hexane.

[0042] In the present application, the ethyl acetate vapor detection gas sensor is a surface porous ZnO material synthesized by hydrothermal and annealing of a mixture of zinc compounds, urea and solvent as a sensitive body, and the purpose of improving detection sensitivity is achieved by the interaction of sensitized ethyl acetate on its surface. It is deposited on the surface of the ceramic tube gold interdigitated electrode by a solution sputtering process to prepare a gas sensor for the detection of ethyl acetate. The resulting sensor has a good response to ethyl acetate vapor, and the actual concentration that can be detected is as low as 1ppm. In addition, the sensor also has the ability to resist interference from other organic vapors, and has a good selective response to ethyl acetate vapor. The sensor can be used as a favorable tool for detecting the freshness of fruits such as apples and strawberries.

[0043] The beneficial effects of this application include:

[0044] 1) This application starts from the chemical interaction between the sensitive material and the target gas, and screens out ZnO materials with unique adsorption and catalytic oxidation activity to it, thereby ensuring the selectivity of the sensitive element.

[0045] 2) The present application achieves high sensitivity response of ZnO to ethyl acetate vapor by sensitizing the porous surface structure, improves its detection limit, and is more conducive to low concentration response in the actual detection process.

[0046] 3) In this application, the response of the gas sensor is affected by many factors, such as the difference in electronic conductivity between gas-sensitive material layers, the diffusion rate and concentration drop caused by the diffusion of gas between different layers, the pore size of semiconductor metal oxide materials, the contact resistance of semiconductor metal oxides, etc. Therefore, as the number of layers increases, the response to the target gas can be improved by optimizing the thickness of the sensitive layer and the consistency of the film layer.

[0047] 4) The sensor and its preparation method of the present application are simple and reliable and have good practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a transmission electron microscopy (TEM) image of the porous ZnO nanorod bundle in Example 1 of the present application.

[0049] Figure 2 This is the response curve of the sensor in Example 2 of the present application tested with 1 ppm ethyl acetate vapor. DETAILED DESCRIPTION

[0050] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0051] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0052] The gas sensor uses porous ZnO nanorod material as the sensitive membrane to achieve high-sensitivity detection of low-concentration ethyl acetate vapor.

[0053] A preparation method of porous ZnO material, the specific steps are as follows

[0054] 1) The molar ratio of zinc compound to urea is 1:0.5-5;

[0055] 2) Disperse the mixture in 40 mL of deionized water;

[0056] 3) Transfer the entire solution into a 50 mL polytetrafluoroethylene-lined autoclave and keep it at 140-200°C for 12 hours;

[0057] 4) The precipitate was collected by centrifugation and washed with deionized water several times. Finally, it was dried at 60°C overnight and annealed at 400-600°C in air for 2 hours to obtain the product.

[0058] A single sensor is prepared by spin coating, and the specific steps are as follows:

[0059] 1) 5 to 100 mg of a porous ZnO material is uniformly dispersed in 0.5 to 10 mL of a solvent (a mixture of one or more of ultrapure water, ethanol, methanol, acetone, acetonitrile, toluene, ethylene glycol, and n-hexane);

[0060] 2) taking a certain volume of the dispersed porous ZnO material described in step 1), dripping it on the surface of N planar interdigital electrodes, and baking it under an infrared lamp at 50-80° C. for 3 hours until the organic solvent is completely volatilized to form a layer of porous ZnO sensitive film; dripping the dispersion liquid on the surface of different ceramic tube interdigital electrodes for different times, and controlling the baking temperature under the infrared lamp at the same time, to obtain multiple sensitive films with different thicknesses and surface densities;

[0061] 3) The sensor works at 200-350℃, and the resistance in the air is 100-2000KΩ;

[0062] 4) The response performance of porous ZnO devices with different thicknesses and surface densities to ethyl acetate was tested, and the sensitive element with the best selectivity and highest sensitivity was selected for real-time detection of low concentration (1 ppm) ethyl acetate.

[0063] Example 1

[0064] 1) Disperse 10 mmol of zinc nitrate hexahydrate, 5 mol of urea and 10 mmol of oxalic acid in 40 mL of deionized water and mix well under magnetic stirring;

[0065] 2) The entire solution was transferred into a 50 mL polytetrafluoroethylene-lined autoclave and maintained at 140 °C for 12 hours;

[0066] 3) The precipitate was collected by centrifugation and washed with deionized water several times. Finally, it was dried at 60°C overnight and annealed at 500°C in air for 2 hours to obtain the product. Figure 1 It can be seen that the prepared ZnO nanomaterial presents a nanorod bundle structure, with a length of about 2500nm and a single nanorod width of about 100nm.

[0067] Example 2

[0068] 1) 5 mg of the porous ZnO nanorod bundles prepared in Example 1 were uniformly dispersed in 5 mL of ethanol by ultrasound;

[0069] 2) Take 5 μL of the dispersed porous ZnO nanorod bundle dispersion and drop it on the surface of a ceramic tube interdigital electrode, and bake it under an infrared lamp at 70°C for 3 hours until the organic solvent is completely volatilized to form a sensitive film; 5 μL of the dispersion is dropped on different ceramic tube interdigital electrodes 1, 2, 3, 4, and 5 times in sequence to obtain 5 sensors with 1 layer, 2 layers, 3 layers, 4 layers, and 5 layers of thickness;

[0070] 3) When the sensor is heated at 300℃, the resistance value is between 20 and 1000KΩ. The response value of the sensor is defined as S=R a / R g , where R a is the resistance of the sensor in air, R g is the resistance of the sensor in the gas to be measured.

[0071] The five gas sensors prepared above were tested for their sensitivity and response to ethyl acetate, and the device with the highest selectivity and responsiveness was optimized. Among them, when the porous ZnO sensor was spin-coated about 4 times, the response to ethyl acetate was the best. The ethyl acetate content emitted by fresh fruits such as apples and strawberries is higher than 1ppm, and the sensor has excellent recognition performance for 1ppm of ethyl acetate. Figure 2 As shown in the figure, the sensor with optimized film thickness has a higher response value to 1ppm ethyl acetate vapor, which can realize the preliminary diagnosis of fruit freshness.

[0072] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A gas sensor for detecting ethyl acetate vapor, characterized in that: The ethyl acetate vapor detection gas sensor uses porous ZnO nanorod material as a sensitive body; The pore size of the porous ZnO nanorod material is 2 to 50 nm; The porous ZnO nanorod material has a length of 2 to 8 μm and a width of 200 to 400 nm.

2. The ethyl acetate vapor detection gas sensor according to claim 1, characterized in that: The operating temperature of the ethyl acetate vapor detection gas sensor is 200-350°C; Preferably, the resistance value of the ethyl acetate vapor detection gas sensor is 100 to 2000 KΩ; Preferably, the ethyl acetate vapor detection gas sensor can detect ethyl acetate concentration of 0.1 to 1 ppm.

3. The method for preparing the ethyl acetate vapor detection gas sensor according to any one of claims 1 to 2, characterized in that: The preparation method comprises: A solution containing the porous ZnO nanorod material is drop-coated on the surface of the interdigital electrode, and infrared baking is performed until the solution is completely volatilized to obtain the ethyl acetate vapor detection gas sensor.

4. The preparation method according to claim 3, characterized in that: The solvent in the solution is selected from at least one of water, ethanol, methanol, acetone, acetonitrile, toluene, ethylene glycol, and n-hexane; Preferably, the mass volume ratio of the porous ZnO nanorod material to the solvent is 5-100 mg: 0.5-10 mL.

5. The preparation method according to claim 3, characterized in that: The number of dripping is 3 to 8 times; Preferably, the temperature of the infrared baking is 50-80°C.

6. The preparation method according to claim 3, characterized in that: The preparation method of the porous ZnO nanorod material comprises: In a sealed container, a mixture containing zinc compounds, urea and a solvent is reacted and annealed to obtain the porous ZnO nanorod material.

7. The preparation method according to claim 6, characterized in that: The zinc compound is selected from at least one of zinc chloride, zinc nitrate and zinc acetate; Preferably, the molar ratio of the zinc compound to urea is 1:0.5-5.

8. The preparation method according to claim 6, characterized in that: The solvent is selected from water and / or ethanol; Preferably, the molar volume ratio of the zinc compound to the solvent is 0.06-1.2 mol: 0.5-20 mL.

9. The preparation method according to claim 6, characterized in that: The reaction temperature is 140-200° C., and the reaction time is 12-20 hours.

10. The preparation method according to claim 6, characterized in that: The annealing temperature is 400-600° C., and the annealing time is 2-4 hours.